Therapeutic Inhibition of Acid-Sensing Ion Channel 1a Recovers Heart Function After Ischemia–Reperfusion Injury. Issue 12 (21st September 2021) - Redd, Meredith A.; Scheuer, Sarah E.; Saez, Natalie J.; Yoshikawa, Yusuke; Chiu, Han Sheng; Gao, Ling; Hicks, Mark; Villanueva, Jeanette E.; Joshi, Yashutosh; Chow, Chun Yuen; Cuellar-Partida, Gabriel; Peart, Jason N.; et al.
Abstract : Background: Ischemia–reperfusion injury (IRI) is one of the major risk factors implicated in morbidity and mortality associated with cardiovascular disease. During cardiac ischemia, the buildup of acidic metabolites results in decreased intracellular and extracellular pH, which can reach as low as 6.0 to 6.5. The resulting tissue acidosis exacerbates ischemic injury and significantly affects cardiac function. Methods: We used genetic and pharmacologic methods to investigate the role of acid-sensing ion channel 1a (ASIC1a) in cardiac IRI at the cellular and whole-organ level. Human induced pluripotent stem cell–derived cardiomyocytes as well as ex vivo and in vivo models of IRI were used to test the efficacy of ASIC1a inhibitors as pre- and postconditioning therapeutic agents. Results: Analysis of human complex trait genetics indicates that variants in the ASIC1 genetic locus are significantly associated with cardiac and cerebrovascular ischemic injuries. Using human induced pluripotent stem cell–derived cardiomyocytes in vitro and murine ex vivo heart models, we demonstrate that genetic ablation of ASIC1a improves cardiomyocyte viability after acute IRI. Therapeutic blockade of ASIC1a using specific and potent pharmacologic inhibitors recapitulates this cardioprotective effect. We used an in vivo model of myocardial infarction and 2 models of ex vivo donor heart procurement and storage as clinical models to show that ASIC1a inhibition improves post-IRI cardiac viability. Use of ASIC1a inhibitors as preconditioning or postconditioning agents provided equivalent cardioprotection to benchmark drugs, including the sodium-hydrogen exchange inhibitor zoniporide. At the cellular and whole organ level, we show that acute exposure to ASIC1a inhibitors has no effect on cardiac ion channels regulating baseline electromechanical coupling and physiologic performance. Conclusions: Our data provide compelling evidence for a novel pharmacologic strategy involving ASIC1a blockade as a cardioprotective therapy to improve the viability of hearts subjected to IRI. Abstract : Supplemental Digital Content is available in the text.